Abiding Dreams - Jaja, Sasi Miet (Literamed Publications Ltd, 2011)
Jasper comes with a passion and flair that shoots him into instant fame. His first play at junior secondary school earns his school a national award. Consequently, he finds a haven in Theatre Arts, but his father insists he must be a medical doctor. Where does his sympathy swing: his passion and talent or his father's choice of career?
Keywords: Fiction